Adolph Sutro's Interior Ocean: A Social Snapshot of 19th-Century Bathing in the United States. Issue 1 (10th May 2021) - Feliz Arrizabalaga, Nerea
Abstract : The story of the Sutro Baths (1894–96) in San Francisco is an early example of encapsulating territory and interiorizing the natural environment. This paper situates Sutro's crystal palace for swimmers within the architectural and social contexts of bathing in the 19th century. The novel typology of these baths transcended previous notions of bathing centers and recreational swimming pools. Their history is linked to evolving forms of leisure and social segregation related to collective swimming pools during this period.